397 Delphi consensus for the UK guideline for management and surveillance of Idiopathic Intracranial Hypertension in children and young people. (17th August 2022) - Amin, Sam; Monaghan, Marie; Moran, Matthew; Forrest, Katharine; Harijan, Pooja; Mehta, Vishal; Mukhtyar, Bina; Muthusamy, Brinda; Parker, Alasdair; Prabhakar, Prab; Whitehouse, William; Krishnakumar, Deepa
Abstract : Aims: Idiopathic Intracranial Hypertension (IIH) is associated with headaches and a potential loss of vision. The prevalence may rise with childhood obesity. As there is no strong evidence to support the way IIH is diagnosed or treated, it is important to establish consensus to guide management and identify areas of uncertainty for further research. We conducted a national Delphi consensus process to inform a national guideline for the management of IIH in children and young people. Methods: The Delphi focused on all aspects of IIH including initial assessments (referral, assessments, laboratory tests, LP, ophthalmology assessments), diagnosis (criteria and terminology) and treatment (including conservative, drug and neurosurgical interventions), follow-up, and surveillance. General paediatricians, paediatric neurologists, ophthalmologists, opticians, neuroradiologists, and neurosurgeons known to have a clinical interest or experience in IIH were invited to take part. The charity IIH-UK contributed to represent patients and their families. A priori consensus was defined as 70% agreement. Results: Recommendations are proposed, based on areas of consensus and relate to aspects of IIH patient management, including: timing of assessment, baseline assessments and investigations, recommended diagnostic criteria, LP and CSF pressure interpretation, neuroimaging, MDT meetings, ophthalmological assessments, method for LP (including use of local and general anaesthetic), dietary recommendations, acetazolamide use and neurosurgical management. (For detail please refer to table 2 ) Conclusion: This new UK consensus for the management and surveillance of IIH provides a realistic and pragmatic approach, based on expert opinion for best clinical care for children and young people with IIH. We hope these recommendations will minimise under and over diagnosis, improve the care offered, and outcomes obtained.